ANALISIS PENGARUH LEVERAGE, UKURAN PERUSAHAAN, FREE CASH FLOW, DAN OPERATING CASH FLOW TERHADAP MANAJEMEN LABA PERUSAHAAN - Nanda Ayu Cahyaning Thyas; Anita Wijayanti; Agni Astungkara (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2022)
This0study aims to0determine and analyze the0effect of leverage, firm0size, free cash flow, and operating cash flow on the earnings management of the0food and beverage subsector companies0listed onitheiIndonesia Stock0 Exchange in the 2015-2018iperiod. The0population in thisistudy were 26icompanies. The technique of0determining the sample using0purposive sampling technique, so0that the final sample obtained was 12 companies. The data0used are secondary0data obtained from the financial0statements of the foodiand0beverage sub-sectoricompanies0listed on theiStock Exchange0in the 2015-20180period. The0data analysis technique used0is the classic assumption0test and multiple0linear regression analysis0with the help of the application0SPSS version 22. Basedion the resultsiof the study showed thatileverage, free cash flow and operating cash flow have noieffect on0earningsimanagement, while0firm size affects earnings management.